2013
DOI: 10.1155/2013/519174
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Chemical Structural Characterisation of a Compound with Antioxidant Activity from the Roots ofSenna italica

Abstract: Senna italica, a member of the Fabaceae family (subfamily Caesalpiniaceae), is widely used in South African traditional medicine to treat a number of disease conditions. Aqueous extracts of the plant are mainly used to treat sexually transmitted infections and intestinal complications. The roots of S. italica were ground to a fine powder and sequentially extracted with n-hexane, dichloromethane, acetone, and methanol using serial exhaustive extraction (SEE) method. Thin layer chromatography was used to analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…These solid antioxidant activities might be attributed to its high total phenolic content as it found to be 474 mg gallic acid equivalent (GAE)/gm extract when estimated by the Folin-Ciocalteu method. Similar results were detected in extracts from Cassia abbreviata and other Senna species rich in proanthocyanidins [ 29 , 30 ].…”
Section: Resultssupporting
confidence: 81%
“…These solid antioxidant activities might be attributed to its high total phenolic content as it found to be 474 mg gallic acid equivalent (GAE)/gm extract when estimated by the Folin-Ciocalteu method. Similar results were detected in extracts from Cassia abbreviata and other Senna species rich in proanthocyanidins [ 29 , 30 ].…”
Section: Resultssupporting
confidence: 81%
“…According to [ 23 ] polyphenolic compound in plants may play a major role in the inhibition AGEs. Resveratrol which has been reported to be present in S. italica extract [ 24 ] might have played a role in the ability of the extract to inhibit protein glycation. Recent studies have also revealed that resveratrol has beneficial effects on the liver by extenuating oxidative stress and downregulation of receptor for AGE (RAGE) expression in the liver of rats with type 2 diabetes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calibrated plastic scale was used to measure the inhibition zones. The test experiment was repeated two times to ensure reliability 11,12 .…”
Section: Methodmentioning
confidence: 99%